2008
DOI: 10.2147/copd.s3036
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence issues in patients treated for COPD

Abstract: Although medical treatment of COPD has advanced, nonadherence to medication regimens poses a significant barrier to optimal management. Underuse, overuse, and improper use continue to be the most common causes of poor adherence to therapy. An average of 40%–60% of patients with COPD adheres to the prescribed regimen and only 1 out of 10 patients with a metered dose inhaler performs all essential steps correctly. Adherence to therapy is multifactorial and involves both the patient and the primary care provider.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
348
3
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(385 citation statements)
references
References 98 publications
13
348
3
8
Order By: Relevance
“…Existing evidence suggests that IT decline over time due to patients forgetting the proper instructions [17,18,29]. However, there was a disparity between the Japanese and the Australian study reviewed about the optimal frequency for IT rechecking and education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing evidence suggests that IT decline over time due to patients forgetting the proper instructions [17,18,29]. However, there was a disparity between the Japanese and the Australian study reviewed about the optimal frequency for IT rechecking and education.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding IT, evidence from Europe shows that up to 50% of patients fail to use their inhalers correctly [17]. Whereas, another review highlighted that nearly 100% of patients perform mistakes in their IT that consequently result in delivering an inadequate dose of the inhaled medication [18]. Poor adherence and suboptimal IT can lead to increased healthcare costs and poor health outcomes.…”
Section: One Of the Main Objectives Of The Global Initiative For Chromentioning
confidence: 99%
“…10 In addition, we included variables possibly associated with adherence including comorbidity, age, gender, visits to the general practitioner, socioeconomic status, psychosocial variables, as well as the year of cohort entry. [18][19][20][21][22][23][24] Appendix- Table 2 (available online) shows a detailed description of all variables. Since previous adherence has been identified as a dominant predictor of future adherence in COPD, 25 we did a fifth sensitivity analysis that did not include previous adherence among possible explanatory variables in the models in order to investigate possible masking of other variables caused by collinearity.…”
Section: Variables Associated With Adherencementioning
confidence: 99%
“…It is possible that Aboriginal people with COPD use more ED services, either because they have higher disease severity 29 that leads to frequent or more severe exacerbations, or due to poorer chronic management for COPD and/or comorbidities that lead to treatment failure and disease relapse that requires frequent emergency care. 30 It is also possible that certain Aboriginal groups use the ED as a "safety net of health care" rather than primary care providers, particularly if they belong to socially and economically disadvantaged communities. 31,32 Data from the 2006 Aboriginal Peoples Survey (APS) showed that the proportion of Aboriginal people who have a regular physician (81%) is lower than the national average in Canada (85%).…”
Section: Discussionmentioning
confidence: 99%